Islamic Equity Investment Under Fiscal Pressure: Evaluating the Impact of Indonesia’s VAT Increase on Sharia-Compliant Markets - Insirat, Mutahira Nur; Syahfir, Hasri Ainun; Darmawati, Darmawati; Rasyid, Syarifuddin (Universitas Muhammadiyah Makassar, 2025)
This study investigates the implications of Indonesia’s Value Added Tax (VAT) increase from 11% to 12%, effective January 1, 2025, on Sharia-compliant equity markets. Introduced as part of broader fiscal reforms, the policy aims to strengthen state revenue while exempting essential goods to minimize public burden. Using a qualitative exploratory approach, the study analyzes the impact of this fiscal shift on investor sentiment, market behavior, and sectoral performance. Results reveal that the VAT hike may reduce consumer purchasing power and corporate profitability, especially in consumption-driven sectors, thus increasing market volatility. Conversely, sectors such as healthcare, technology, and halal fintech demonstrate resilience and alignment with Sharia principles. From an Islamic finance perspective, the VAT policy is acceptable if it fulfills the objectives of maqasid al-shariah, particularly justice and protection for vulnerable groups. The study concludes that incorporating ethical investment frameworks and promoting strategic sectoral diversification can help Islamic equity investors manage risks and harness long-term opportunities amid fiscal tightening.